Household fish consumption in relation to fishing practices and fish production in flood plains of Bangladesh - Tsai, Chu Fa; Ali, Mohammad Youssuf; Ahsan, Kamrul; Alam, Sardar S (Indian Journal of Fisheries, 2011)
Situated in the Ganges River Delta,Bangladesh has one of the richest and largestflood-plainÂ· systems in the world (Rahman1989). Its total areawas'eltimated to b.: 2 946953 ha, occupying 72.81 % of the inland waterarea, and prooucfngltbout 50% of the total fishproduction of inland open water capturefisheries (Bangladesh Fisheries ResourcesSurvey System 1988).